Evaluating Dysfunction in Fever-Induced Paroxysmal Weakness and Encephalopathy - Fumikazu Sano; Toshimichi Fukao; Hideaki Yagasaki; Hideaki Kanemura; Takeshi Inukai; Yoshimi Kaga; Takaya Nakane (MDPI AG, 2023)
Heterozygous variants in the ATP1A3 gene are linked to well-known neurological phenotypes. There has been growing evidence for a separate phenotype associated with variants in residue Arg756-fever-induced paroxysmal weakness and encephalopathy (FIPWE) or relapsing encephalopathy with cerebellar ataxia (RECA). With only about 20 cases being reported, the clinical features associated with mutations at Arg756 have not been fully elucidated. We report a case of FIPWE with a p.Arg756Cys change in the ATP1A3 gene and a comparison of the clinical features, including electrophysiological examination, with previous cases. The 3-year-old male patient had normal psychomotor development, presenting with recurrent symptoms of generalized hypotonia with loss of gait, mutism, and dystonic movements only during febrile illnesses since 19 months of age. At 2.7 years of age, a third neurological decompensation episode occurred, during which electroencephalography (EEG) did not reveal high voltage slow waves or epileptiform discharge. Nerve conduction studies (NCS) also did not show latency delay or amplitude reduction. ATP1A3 exon sequencing showed a heterozygous p.Arg756Cys mutation. While the patient experienced repeated encephalopathy-like episodes, including severe hypotonia during febrile illness, EEG and NCS did not reveal any obvious abnormalities. These electrophysiological findings may represent an opportunity to suspect FIPWE and RECA.